One-pot and metal-free synthesis of 3-arylated-4-nitrophenols via polyfunctionalized cyclohexanones from β-nitrostyrenes - Asahara, Haruyasu; Hiraishi, Minami; Nishiwaki, Nagatoshi (Beilstein Journal of Organic Chemistry, 2020)
β-Nitrostyrenes underwent a Diels–Alder reaction with Danishefsky’s diene to afford cyclohexenes together with the corresponding hydrolyzed products, 3-arylated-5-methoxy-4-nitrocyclohexanones. When the reaction was conducted in the presence of water, the cyclohexenes were efficiently hydrolyzed into cyclohexanones. Subsequent aromatization by heating the cyclohexanone with a catalytic amount of iodine in dimethyl sulfoxide gave 3-arylated-4-nitrophenols. The reaction of nitrostyrenes with Danishefsky’s diene could be conducted in one pot to directly afford the corresponding nitrophenols. Moreover, a heteroaryl group, e.g., a thienyl group could be introduced into the nitrophenol framework.
Keywords: 3-arylated-4-nitrophenol; Danishefsky’s diene; Diels–Alder reaction; nitroalkene; polysubstituted cyclohexanone